The Right to Access Information and Data Collection on Social Assistance in Sidioarjo Regency - Probojati Bayu Herlambang; Wiwik Afifah (Proceeding International Conference on Religion, Science and Education, 2023)
The right to access information and data collection on social assistance is a means of information that is always needed by the community. The right to access information and data collection aims to find out the latest condition of beneficiary family members who receive social assistance such as PKH, BLT and BPNT. With the updating of this data it serves as basic data for social protection programs, in this case the data collection is used for verification, distribution and termination of social assistance. As time went on, many problems emerged both in the region and in the district, in collecting data there were still many who did not collect data directly from KPM households, but only made observations so that the elements of like and dislike still existed and to find out the problems that existed in Candipari Village regarding information and data collection on social assistance. So the purpose of our research is to determine the effectiveness of policies in terms of information and data collection on social assistance in Candipari Village, Sidoarjo Regency. The method used in this research is empirical juridical. In conducting research, the authors obtained information by making observations about the process of distributing aid, interviews with the Candipari sub-district community starting with village officials, aid operators, and beneficiary and non-assistance communities which in the future were used to answer several existing legal issues. The results of the findings in this study are that the implementation of the information process and data collection on social assistance in the village of Candipari, Sidoarjo Regency has been running quite effectively.